Heavy Metal Stress, Signaling, and Tolerance Due to Plant-Associated Microbes: An Overview - Tiwari, Shalini; Lata, Charu (Frontiers in Plant Science, 2018)
Several anthropogenic activities including mining, modern agricultural practices and industrialisation have long term detrimental effect on our environment. All these factors lead to increase in heavy metal concentration in soil, water and air. Soil contamination with heavy metals cause several environmental problems and imparts toxic effect on plant as well as animals. In response to these adverse conditions plants evolve complex molecular and physiological mechanisms for better adaptability, tolerance and survival. Nowadays conventional breeding and transgenic technology are being used for development of metal stress resistant varieties which however, are time consuming and labor intensive. Interestingly the use of microbes as an alternate technology for improving metal tolerance of plants is gaining momentum recently. The use of these beneficial microorganisms is considered as one of the most promising methods for safe crop-management practices. Interaction of plants with soil micro-organisms can play a vital role in acclimatizing plants to metalliferous environments, and can thus be explored to improve microbe-assisted metal tolerance. Plant-associated microbes decrease metal accumulation in plant tissues and also help to reduce metal bioavailability in soil through various mechanisms. Nowadays, a novel phytobacterial strategy i.e. genetically transformed bacteria has been used to increase remediation of heavy metals and stress tolerance in plants. This review takes into account our current state of knowledge of the harmful effects of heavy metal stress, the signalling responses to metal stress and the role of plant-associated microbes in metal stress tolerance. The review also highlights the challenges and opportunities in this continued area of research on plant-microbe-metal interaction.